The Dynamic Role of Fiscal and Monetary Policies on Energy Efficiency in Indonesia - Aliasuddin, Aliasuddin; Effendi, Rustam; Samsudin, Hazman; Rahmi, Nanda; Fachrurrozi, Kamal (International Journal of Energy Economics and Policy, 2024)
This study analyzes the dynamic influence of monetary and fiscal policies on energy efficiency in Indonesia. Quarterly data from the first quarter of 2000 to the fourth quarter of 2023 with a sample size of 96 quarters and the ARDL model are used in this study. The results of the short-term dynamic study show that monetary and fiscal policies significantly affect energy efficiency in Indonesia. However, dynamic economic growth does not affect energy efficiency. Furthermore, there is no difference in the influence of dynamic monetary and fiscal policies on energy efficiency in Indonesia. The monetary authority and the government of Indonesia must use monetary and fiscal policies to improve efficiency in Indonesia. Energy efficiency is very important not only in the use of natural resources but also in environmental damage due to inefficient energy use.